Phylogenomics reveals multiple losses of nitrogen-fixing root nodule symbiosis - Griesmann, Maximilian; Chang, Yue; Liu, Xin; Song, Yue; Haberer, Georg; Crook, Matthew B.; Billault-Penneteau, Benjamin; Lauressergues, Dominique; Keller, Jean; Imanishi, Leandro; Roswanjaya, Yuda Purwana; Kohlen, Wouter; et al. (Science (American Association for the Advancement of Science), 2018)
A symbiosis between certain bacteria and their plant hosts delivers fixed nitrogen to the plants. Griesmann et al. sequenced several plant genomes to analyze why nitrogen-fixing symbiosis is irregularly scattered through the evolutionary tree (see the Perspective by Nagy). Various genomes carried traces of lost pathways that could have supported nitrogen-fixing symbiosis. It seems that this symbiosis, which relies on multiple pathways and complex interorganismal signaling, is susceptible to selection and prone to being lost over evolutionary time. Science , this issue p. eaat1743 ; see also p. 125 Genome-wide comparative analysis across species reveals the fragility of the plant-bacterial symbiosis needed for nitrogen fixation. The root nodule symbiosis of plants with nitrogen-fixing bacteria affects global nitrogen cycles and food production but is restricted to a subset of genera within a single clade of flowering plants. To explore the genetic basis for this scattered occurrence, we sequenced the genomes of 10 plant species covering the diversity of nodule morphotypes, bacterial symbionts, and infection strategies. In a genome-wide comparative analysis of a total of 37 plant species, we discovered signatures of multiple independent loss-of-function events in the indispensable symbiotic regulator NODULE INCEPTION in 10 of 13 genomes of nonnodulating species within this clade. The discovery that multiple independent losses shaped the present-day distribution of nitrogen-fixing root nodule symbiosis in plants reveals a phylogenetically wider distribution in evolutionary history and a so-far-underestimated selection pressure against this symbiosis.